Il linguaggio del territorio fra principe e comunità - Isabella Lazzarini (Firenze University Press, 2021)
In April 1479, the communities of the marquisate of Mantua pronounced for the first time a general oath of fealty to Federico Gonzaga, the third marquis, inaugurating a custom that was to be repeated with relative regularity in the following decades every time a Prince died. It was a practice which was fairly new for the Gonzago marquisate, at least in this capillary and general extension to the entire body of the State. The significance of an innovation of this kind deserves attention, as do the genesis and the partial forms that preceded this mature expression. This book comprises an edition of the entire related documentary corpus, complete with photographic reproductions of the individual documents, and preceded by a substantial introduction in which the event is described, placed in context and interpreted from various points of view.